(untitled) (Journal of the College of Basic Education, 2023)
Apparent molal volume ɸv, apparent molal volumes at infinite dilution ɸov ,the slope Sv and viscosity B and D coefficients for Threonine (Thr) in (2-10)% w/w aqueous Dimethyl Sulfoxide (DMSO) solvents have been calculated respectively from the density and viscosity measurements at different temperatures 298.15,303.15,308.15and 313.15 K. The results are discussed in the light of solute-solvent and solute-solute interaction, and shows that Threonine behave as structure-breaker in aqueous DMSO solvent.